Mangrove Community Structure In Teluk Buo, Bungus, Padang Regency, West Sumatera - Faristy, Annisya Fhadilah Putri; Lailani Eka Putri, Irma (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Mangroves are forest vegetation that grows between the tidal lines, so mangrove forests are also called tidal forests. The existence of mangrove forests in the ecosystem is very important because it has ecological and economic potential. The location of the mangrove ecosystem in a transitional area between sea and land areas causes mangroves to frequently experience disturbance for human purposes and results in mangrove areas experiencing damage and land narrowing which has an impact on decreasing their diversity. This research aims to analyze the structure of the mangrove community in the research area. The method used in this research is the quadratic method (Quadrat Sampling Technique) by creating 6 plots facing each other. Observation of mangrove vegetation uses a plot measuring 10 x 10 meters for trees, 5 x 5 meters for saplings and 2 x 2 meters for seedlings. The results that can be concluded from this research are that the mangrove forest community in Teluk Buo consists of Rizophora apiculata, Lumnitzera littorea, Brugeira gymnorhiza, Setaria palmifolia, Euterpe oleracea mart, Nypa Fruticans, and Bruguiera cylindrical. The Rhizophora apiculata species dominates in the study area, characterized by the highest importance at all growth levels. INP at tree level was 166%, sapling 219% and seedling 127%. The diversity index (H') value in the study area is low (1.749) with a high level of uniformity (0.8986).